Genetic Rodent Models of Obesity-Associated Ovarian Dysfunction and Subfertility: Insights into Polycystic Ovary Syndrome - Huang-Doran, Isabel; Franks, Stephen (Frontiers in Endocrinology, 2016)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy affecting women, and a leading cause of female infertility worldwide. Defined clinically by the presence of hyperandrogenemia and oligomenorrhoea, PCOS represents a state of hormonal dysregulation, disrupted ovarian follicle dynamics, and subsequent oligo- or anovulation. The syndrome’s prevalence is attributed at least partly to a well-established association with obesity and insulin resistance (IR). Indeed, the presence of severe PCOS in human genetic obesity and IR syndromes supports a causal role for IR in the pathogenesis of PCOS. The molecular mechanisms underlying this causality, however, as well as the important role of hyperandrogenemia, remain poorly elucidated. As such, treatment of PCOS is necessarily empirical, focusing on symptom alleviation. The generation of knockout and transgenic rodent models of obesity and IR offer a promising platform in which to address mechanistic questions about reproductive dysfunction in the context of metabolic disease. The impact of primary perturbations in rodent gonadotrophin or androgen signaling has been similarly interrogated. The insights gained from such models, however, have been limited by the relatively poor fidelity of rodent models to human PCOS. In this minireview we evaluate the ovarian phenotypes associated with rodent models of obesity and IR, including the extent of endocrine disturbance, ovarian dysmorphology and subfertility. We compare them to both human PCOS and other animal models of the syndrome (genetic and hormonal), explore reasons for their discordance and consider the new opportunities that are emerging to better understand and treat this important condition.